2014
DOI: 10.1002/biof.1164
|View full text |Cite
|
Sign up to set email alerts
|

Nutraceuticals and regulation of adipocyte life: Premises or promises

Abstract: Obesity is the actual worldwide health threat, that is associated with an increased number of metabolic disorders and diseases. Following the traditional hypothesis stating that in obesity hypertrophic adipocytes trigger the adipose tissue hyperplasia, strategies to treat obesity have increased fat researches of the molecular processes that achieve adipocyte enlargement and formation that finally increase body fat mass. Moreover, a new cell type was recently identified, the "brite" adipocyte that presents a un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 208 publications
(388 reference statements)
1
36
0
Order By: Relevance
“…The adipocyte lifecycle, including proliferation, differentiation, and adipogenesis, has been recognized as a potential target for the prevention and treatment of obesity . Here, we found that although Calebin‐A displayed a slightly cytotoxic effect in 3T3‐L1 preadipocytes at the highest concentration, it did not cause cell death in adipocytes during differentiation.…”
Section: Discussionmentioning
confidence: 70%
“…The adipocyte lifecycle, including proliferation, differentiation, and adipogenesis, has been recognized as a potential target for the prevention and treatment of obesity . Here, we found that although Calebin‐A displayed a slightly cytotoxic effect in 3T3‐L1 preadipocytes at the highest concentration, it did not cause cell death in adipocytes during differentiation.…”
Section: Discussionmentioning
confidence: 70%
“…In this context, natural products have been studied for their role in the regulation of adipocyte life cycle [29]. Phytochemicals can target different stages in the adipocyte life cycle by decreasing adipogenesis, inducing lipolysis, inducing adipocyte-apoptosis and by inducing transdifferentiation of white to brown-like adipocytes [30]. While the terms nutraceuticals, phytochemicals and bioactives are often used synonymously, it should be noted that phytochemicals are non-nutrient bioactive compounds found in fruits, vegetables and other parts of plants.…”
Section: Phytochemicals In Obesitymentioning
confidence: 99%
“…Currently, adipose tissue is also considered an endocrine organ capable of releasing a variety of bioactive substances known as adipose-derived secreted factors or adipokines (Wang et al, 2008;Colitti and Grasso, 2014). The WAT is innervated by the sympathetic nervous system (SNS), although less extensively than brown adipose tissue (BAT) (Bartness et al, 2001).…”
mentioning
confidence: 99%